Original research: Second IVIg course in Guillain-Barré syndrome with poor prognosis: the non-randomised ISID study. Issue 2 (5th October 2019) - Verboon, Christine; van den Berg, Bianca; Cornblath, David R; Venema, Esmee; Gorson, Kenneth C; Lunn, Michael P; Lingsma, Hester; Van den Bergh, Peter; Harbo, Thomas; Bateman, Kathleen; Pereon, Yann; Sindrup, Søren H; et al.
Abstract : Objective: To compare disease course in patients with Guillain-Barré syndrome (GBS) with a poor prognosis who were treated with one or with two intravenous immunoglobulin (IVIg) courses. Methods: From the International GBS Outcome Study, we selected patients whose modified Erasmus GBS Outcome Score at week 1 predicted a poor prognosis. We compared those treated with one IVIg course to those treated with two IVIg courses. The primary endpoint, the GBS disability scale at 4 weeks, was assessed with multivariable ordinal regression. Results: Of 237 eligible patients, 199 patients received a single IVIg course. Twenty patients received an 'early' second IVIg course (1–2 weeks after start of the first IVIg course) and 18 patients a 'late' second IVIg course (2–4 weeks after start of IVIg). At baseline and 1 week, those receiving two IVIg courses were more disabled than those receiving one course. Compared with the one course group, the adjusted OR for a better GBS disability score at 4 weeks was 0.70 (95%CI 0.16 to 3.04) for the early group and 0.66 (95%CI 0.18 to 2.50) for the late group. The secondary endpoints were not in favour of a second IVIg course. Conclusions: This observational study did not show better outcomes after a second IVIg course in GBS with poor prognosis. The study was limited by small numbers and baseline imbalances. Lack of improvement was likely an incentive to start a second IVIg course. A prospective randomised trial is needed to evaluate whether a second IVIg course improves outcome in GBS.